Navigating The Trade Landscape: A Latin American Perspective Building on the WTO 13th Ministerial Conference - Piñeiro, Valeria (International Food Policy Research Institute (IFPRI), 2024)
It analyzes the current state of agricultural trade negotiations in the context of geopolitical changes and proposes the reforms and frameworks needed to improve the effectiveness of trade agreements, particularly in light of recent global challenges. The methodology employed in the paper includes literature review, thematic analysis and expert opinions. The main points addressed are the need for institutional reforms, the focus on agricultural trade. Defining policies for holding public stocks to support net importing countries in the midst of global uncertainties. It also identifies some geopolitical implications. Finally, there is a call to action for member countries to engage in meaningful discussions and reforms to adapt to the changing trade landscape.